Kadar Fe Organik dan P Tersedia pada Tanah Sawah Rawa Lebak yang Diaplikasi Kompos dan Pengelolaan Air di Poso - Mowidu, Ita (Universitas Sebelas Maret, 2018)
Non-tidal swamp rice field in Poso contain total Fe in a very high amount, ranging from 1,16% to 2,26%. In a reductive or very reductive condition, Fe solubility will be extremely high beyond the level where paddy can tolerate, hence causing toxicity in paddy. Application of compost is expected to chelate Fe and form organic Fe to decrease toxic effect in paddy. A greenhouse experiment was done treatment by 5 ton/ha of straw compost and cocoa pod compost in various combination to non-tidal swamp rice field in Korobono Poso regency. Under this factorial treatment, the first factor was composition of compost (100% straw compost, 75% straw compost + 25% cocoa pods compost, 50% straw compost + 50% cocoa pods compost, 25% straw compost + 75% cocoa pods compost, and 100% cocoa pods compost), and the second factor was water management (saturated irrigation and intermittent), arranged under completely randomized design (CRD). The observed component was the level of organic Fe and available P in soil. The research finding showed that the application of compost to non-tidal swamp rice field in Poso increased the level of organic Fe and available P in soil. The level of organic Fe and available P in soil with saturated irrigation was higher than with intermittent irrigation. The increased organic Fe tended to increased available P in the soil in non-tidal swamp rice field in Poso.